NCAM (CD56) Expression in keratin-producing odontogenic cysts: aberrant expression in KCOT - Vera-Sirera, Beatriz (Head Face Med, 2015)
OBJECTIVE: To investigate immunohistochemically the expression of neural cell adhesion molecule (NCAM), which has been identified as a signaling receptor with frequent reactivity in ameloblastomas (AB), in a series of keratin-producing odontogenic cysts (KPOCs). MATERIAL AND METHODS: Immunohistochemical expression of NCAM, using a monoclonal antibody, was determined in a series of 58 KPOCs comprising 12 orthokeratinized odontogenic cysts (OOCs) and 46 keratocystic odontogenic tumors (KCOTs), corresponding to 40 non-syndromic KCOT (NS-KCOTs) and 6 syndromic KCOT (S-KCOTs), associated with nevic basocellular syndrome (NBCS). RESULTS: NCAM expression was negative in all OOCs, but 36.45% of KCOTs exhibited focal and heterogeneous expression at the basal cell level, as well as in basal budding areas and the basal cells of daughter cysts. The latter two locations were especially applicable to S-KCOTs, with focal NCAM reactivity occurring in 66.66% of cases. CONCLUSIONS: Aberrant NCAM expression, in KCOTs but especially in S-KCOTs, together with its immunomorphological location, suggests that this adhesion molecule and signaling receptor plays a role in the pathogenesis of KCOTs, with a probable impact on lesional recurrence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13005-015-0060-2) contains supplementary material, which is available to authorized users.